THE INFLUENCE OF EARNINGS PER SHARE (EPS) AND RETURN ON EQUITY (ROE) ON STOCK PRICE WITH PRICE EARNING RATIO (PER) AS A MODERATION VARIABLE IN CONSTRUCTION SUB SECTOR COMPANIES AND BUILDING LISTED ON INDONESIA STOCK EXCHANGE - Ammy, Baihaqi; Azizah, Siti (CV. Radja Publika, 2021)
This research aims to prove whether there is an effect To test the Price Earning Ratio (PER) in moderating the effect of Return On Equity (ROE) on stock prices in construction and building sub-sector companies listed on the Indonesia Stock Exchange in 2015 – 2020. This type of research is associative research. The sampling technique used is purposive sampling. The data used is secondary data in the form of financial statements of construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) obtained through the website www.idx.co.id. This data will be analyzed using multiple linear regression analysis method, which is a descriptive statistical method used to analyze data for more than two research variables. Classical assumption test used is normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. To test regression with moderating variablesModerating Regression Analysis (MRA) Test. The hypothesis testing used is t-test, F-test, and the coefficient of determination (R2). This study resulted in five findings as proposed in the research hypothesis. First,Earnings Per Share (EPS) significant effect on stock prices in the construction and building sub-sector companies listed on the Indonesia Stock Exchange. Second, Return On Equity (ROE) has a significant effect on stock prices in construction and building sub-sector companies listed on the Indonesia Stock Exchange. Third, Earning Per Share (EPS) and Return On Equity (ROE) simultaneously have a significant effect on stock prices in construction and building sub-sector companies listed on the Indonesia Stock Exchange. Fourth,Variable interaction results Earning Per Share (EPS) with Price Earning Ratio (PER) is a moderating variable, so Price Earning Ratio (PER) can strengthen the relationship Earning Per Share (EPS) to stock prices. Fifth,Variable interaction results Return On Equity (ROE) with Price Earning Ratio (PER) can strengthen the relationship Return On Equity (ROE) to stock prices.